Moral Forming And Character Of Participants In The Al-Quran Perspective - Ela Syahfriani; Mardia Ulfa Hasibuan; Robie Fanreza (Proceeding International Seminar of Islamic Studies, 2019)
Moral and character degradation is quite alarming in Indonesia, especially among students. As a result of moral and character degradation this causes increased delinquency in students in committing acts not commendable either in schools or in the community. Efforts to suppress moral and character degradation are by forming students' character by cultivating reading and applying the Koran to them. With the activities of cultivating the Koran as a lifestyle for students will provide solutions to moral degradation in students. This activity is expected to provide solutions and help teachers in overcoming moral and character degradation in students.